Perbandingan Hasil Belajar Santriwan dan Santriwati Pada Mata Pelajaran Akidah Akhlak di Madrasah Diniyah Awwaliyah Baiturrahman, Rumbai, Kota Pekanbaru - Muhammad Hafid; Nur Aisyah Zulkifli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The objective of this study is to analyze and compare the cognitive learning outcomes of the Akidah Akhlak subject between male and female students enrolled at Madrasah Diniyah Awwaliyah (MDA) Baiturrahman, Rumbai, Pekanbaru City. A quantitative approach was utilized, employing an ex post facto design. The entire population, comprising 21 students from grades 1 to 4, served as the subjects of this research study (total sampling). The data were collected through the documentation of semester exam results/report cards. A subsequent descriptive analysis revealed that the mean score attained by female students (85.00) was marginally higher than that of their male counterparts (82.71). However, subsequent to the fulfillment of the normality and homogeneity tests, the Independent Samples T-Test hypothesis test yielded a significance value (Sig. 2-tailed) of 0.611. Given that the p-value is greater than 0.05, the Null Hypothesis (H0) is accepted. The findings of this study indicate that there is no statistically significant difference in the average cognitive learning outcomes of the Akidah Akhlak subject based on gender at MDA Baiturrahman Rumbai, Pekanbaru. Keywords: The following learning outcomes have been identified: Akidah Akhlak, Gender, Male Students, and Female Students.